Adenosine-Assisted Management of Intracranial Aneurysm - Thakore, Bhoomika; Goraksha, Shwetal; Monteiro, Joseph N. (Journal of Neuroanaesthesiology and Critical Care, 2019)
Cerebral aneurysms can be complex and variable in size, position, and morphology, resulting in difficult surgical exposure and secure clip placement. They have a high mortality rate when ruptured, and though endovascular techniques have emerged to tackle this, surgical clip ligation remains the preferred modality for some aneurysms. Various techniques that help the surgeon dissect the aneurysmal dome and apply the clip are temporary clip ligation of proximal vessels, deep hypothermic circulatory arrest, and balloon suction decompression. All of them require significant logistics and result in increased morbidity and mortality. Adenosine is a suitable alternative for inducing a temporary flow arrest, causing a short period of controlled hypotension. Its rapid onset and offset property along with low incidence of adverse events makes it an ideal agent in this regard. We present here a review on its use, contraindications, safety profile, and future applications.
Keywords: adenosine; cerebral aneurysm; flow arrest